Functional outcomes at 12 months for patients with traumatic brain injury, intracerebral haemorrhage and subarachnoid haemorrhage treated in an Australian neurocritical care unit: A prospective cohort study. Issue 6 (November 2020) - Fitzgerald, Emily; Hammond, Naomi; Tian, David H.; Bradford, Celia; Flower, Oliver; Harbor, Kelly; Johnson, Phil; Lee, Richard; Parkinson, Jonathon; Tracey, Ashleigh; Delaney, Anthony
Abstract: Background: Acute severe brain injury is associated with significant morbidity and mortality. Patients and their families need accurate information regarding expected outcomes. Few studies have reported the long-term functional outcome of patients with acute severe brain injury treated in an Australian neurocritical care unit. Objective: The objective of this study was to describe 12-month functional outcomes (using the extended Glasgow Outcome Scale) of patients with acute severe brain injury treated in an Australian neurocritical care unit. Methods: This was a single-centre prospective cohort study. Patients with a diagnosis of traumatic brain injury, subarachnoid haemorrhage or intracranial haemorrhage admitted between 2015 and 2019 were enrolled. Results: In total, 915 participants were enrolled during the 51-month study period. Of the cohort, 403 (44%) were admitted after traumatic brain injury, 274 (30%) after subarachnoid haemorrhage and 238 (26%) after intracranial haemorrhage. The median duration of intensive care admission was 5 days (interquartile range: 2–13), 458 (50%) received invasive ventilation, 417 (46%) received vasopressor support and 286 (31%) received an external ventricular drain. At discharge from intensive care, 150 of 915 (16.4%) had died, and the in-hospital mortality was seen in 191 of 915 patients (20.9%). Favourable functional outcome, as defined by an extended Glasgow Outcome Scale score of 5–8, was reported in 358 of available 795 patients (45.0%) at six months and in 311 of 672 available patients (46.3%) at 12 months. Those with intracranial haemorrhage reported the highest rates of unfavourable outcomes with 112 of 166 patients (67.4%) at 12 months. Conclusions: In this selected population, admission to a neurocritical care unit was associated with significant resource use. At 12 months after admission, almost half of those admitted to an Australian neurocritical unit with traumatic brain injury, subarachnoid haemorrhage and intracerebral haemorrhage report a good functional outcome.